The European dilemma: evaluating the implications of UEFA Europa League participation on English Premier League clubs. (10th November 2017) - Cox, Adam; Gilmore, Sarah; Graham, Alan
Abstract : For clubs qualifying for the UEFA Europa League, participation generates a series of tensions. UEFA has provided financial rewards for those clubs, but with qualification comes additional pressures on playing squads which are often less able to deal with the performative demands of an extra competition, as they generally possess fewer financial resources compared with teams gaining Champions League qualification. This paper evaluates these conflicting tensions. The study takes a detailed quantitative analysis of the costs and benefits for four Premier League clubs that have repeatedly participated in the Europa League over eight seasons. It demonstrates a positive financial benefit of participation, but this is only significant if the club progresses to the later competition stages and has a robust playing squad. This research fills a gap in a lack of analysis based on reliable empirical data as to the impact of participation in this competition on clubs.